Medicinal species of the genus Zanthoxylum (Rutaceae) in Brazil (Research, Society and Development, 2022)
The genus Zanthoxylum (Rutaceae, Sapindales) has about 225 species in the world. In Brazil, there are 27 species, with several used mainly in landscaping and urban and rural afforestation, in addition to beekeeping, source of wood and medicinal use. The research aimed to carry out a survey of the species of Zanthoxylum used in Brazilian folk medicine, as well as to systematize the synonyms, popular names, infirmities, main chemical compounds and phytogeographic information for the species. It took place between December 2021 and June 2022, with the survey of articles, books, dissertations and theses available on the internet or in print with information on medicinal uses and chemical compounds for Zanthoxylum species, in addition to specialized websites with photographs, synonyms, popular names, phytogeographic information and distribution maps. The research presents 14 medicinal species of Zanthoxylum in Brazil (Z. caribaeum, Z. ekmanii, Z. fagara, Z. gardneri, Z. kleinii, Z. monogynum, Z. nemorale, Z. pentandrum, Z. petiolare, Z. rhoifolium, Z. riedelianum, Z. rigidum, Z. stelligerum, Z. tingoassuiba), all native, 98 synonyms and 46 popular names, highlighting limãozinho (8 spp.), mamica-de-porca (6 spp.) and laranjinha (5 spp.). They are used for 35 medicinal purposes, mainly inflammation, toothache, vaginal inflammation, menstrual cramps, earache, fever, sexual impotence, sweating, gastric movements, rheumatism, skin problems, vitiligo, pain, tonic and worms. The research shows the medicinal importance of the genus in Brazil, however, new ethnobotanical works may bring medicinal information for species with little or no information.